2014
DOI: 10.7777/jkfs.2014.34.3.107
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Permeability of Green Sand Mould by Performing Sensitivity Analysis on Neural Networks Model

Abstract: Permeability is the ability of a material to transmit fluid/gases. It is an important material property and it depends on mould parameters such as grain fineness number, clay, moisture, mulling time, and hardness. Modeling the relationships among these variable and interactions by mathematical models is complex. Hence a biologically inspired artificial neural-network technique with a back-propagation-learning algorithm was developed to estimate the permeability of green sand. The developed model was used to pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Smooth uniform casting surface and low permeability was always the result of fine sand particles, whereas rough casting surface and higher permeability were obtained with the coarse sand particles. Further, size and shape of sand grains, water, clay content and degree of ramming will control the mould permeability [14]. Observations made from the above literature shows that the sand grain size and shape, setting time, binder (resin and hardener) type and quantity, and mould additives (coal dust, iron dust, sawdust, sea coal, wood floor, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smooth uniform casting surface and low permeability was always the result of fine sand particles, whereas rough casting surface and higher permeability were obtained with the coarse sand particles. Further, size and shape of sand grains, water, clay content and degree of ramming will control the mould permeability [14]. Observations made from the above literature shows that the sand grain size and shape, setting time, binder (resin and hardener) type and quantity, and mould additives (coal dust, iron dust, sawdust, sea coal, wood floor, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…bulk density, porosity, permeability (P), shear and compression strength (CS)). Porosity in castings was the result of trapping of air due to poor permeability [14]. The trapped air within the mould creates pressure when the permeability is not sufficient.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Mold pressure was found to increase when the permeability was not sufficient and led to gas porosity in castings. 17 The permeability of molding sand depends on sand grain size and shape, clay content, water quantity, and degree of hardness. 17 The above observations lead to the conclusions that binder and hardener content, size and shape of mold sand, refining additives, and ramming influence the mold sand properties (permeability, mold hardness, compression strength, collapsibility, gas evolution, and so on), and thereby affect the dimensional accuracy, surface finish, mechanical, and microstructure of castings.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 However, the molds with lower permeability will result in porous castings. 17 The influence of binder and hardener content on molding strength, gas evolution (GE), and casting microstructure was studied by researchers. [12][13][14] Molding strength improved with increase in resin content, but affected mold collapsibility resulting in hot tears.…”
Section: Introductionmentioning
confidence: 99%
“…The sand grain size and shape was found to affect mould permeability and casting surface finish [8][9]. Casting porosity was reported to increase with the increase in mould pressure, and the compacted mould does not allow the generated gasses to escape out [10]. Kandelwal and Ravi [11] found that core shrinkage and hardness are significantly influenced by the amount of binder content, than hardener.…”
Section: Introductionmentioning
confidence: 99%